Determination of genotoxic potencies of pyrrolizidine alkaloids in HepaRG cells using the γH2AX assay. (September 2019) - Louisse, Jochem; Rijkers, Deborah; Stoopen, Geert; Holleboom, Wendy Jansen; Delagrange, Mona; Molthof, Elise; Mulder, Patrick P.J.; Hoogenboom, Ron L.A.P.; Audebert, Marc; Peijnenburg, Ad A.C.M.
Abstract: Pyrrolizidine alkaloids (PAs) are secondary metabolites from plants that have been found in substantial amounts in herbal supplements, infusions and teas. Several PAs cause cancer in animal bioassays, mediated via a genotoxic mode of action, but for the majority of the PAs, carcinogenicity data are lacking. It is assumed in the risk assessment that all PAs have the same potency as riddelliine, which is considered to be one of the most potent carcinogenic PAs in rats. This may overestimate the risks, since many PAs are expected to have lower potencies. In this study we determined the concentration-dependent genotoxicity of 37 PAs representing different chemical classes using the γH2AX in cell western assay in HepaRG human liver cells. Based on these in vitro data, PAs were grouped into different potency classes. The group with the highest potency consists particularly of open diester PAs and cyclic diester PAs (including riddelliine). The group of the least potent or non-active PAs includes the monoester PAs, non-esterified necine bases, PA N -oxides, and the unsaturated PA trachelanthamine. This study reveals differences in in vitro genotoxic potencies of PAs, supporting that the assumption that all PAs have a similar potency as riddelliine is rather conservative. Highlights: More insight in relative potencies of pyrrolizidine alkaloids (PAs) is needed. In vitro genotoxicity of 37 PAs was determined by measuring γH2AX induction in HepaRG cells. 26 PAs concentration-dependently induced γH2AX at non-cytotoxic concentrations. Relative potencies were determined using Benchmark Dose Modelling. Based on these relative potencies, PAs were divided in potency classes.